Enablers and barriers of General Practitioner’s choice of additional skills training: a mixed-methods study - Seidu, Abdul-Aziz; Anderson, Emma M.; Mason, Hannah; Albert, Francis A.; Alele, Faith O.; Heggarty, Paula; Hollins, Aaron; Gupta, Tarun Sen; McArthur, Lawrie; Hays, Richard; Malau-Aduli, Bunmi S. (Frontiers in Medicine, 2025)
IntroductionAdditional skills training (AST) is a prerequisite for rural generalist training in Australia, where Rural Generalists (RGs) undergo specialized training in a distinct discipline for a period of 12 months. This study investigated the perspectives of General Practitioners (GPs) regarding the factors influencing their selection of AST programs.MethodsUsing a sequential explanatory mixed methods approach, quantitative survey data and qualitative interview data were collected. Quantitative data was analyzed using frequencies, percentages, mean and standard deviations, while thematic analysis was employed for the qualitative data.ResultsA total of 106 respondents completed the survey, with 13 participating in interviews (supervisors n = 5; registrars n = 8). GPs perceived AST as beneficial in improving patient outcomes (57.5%) and enhancing patient satisfaction (49.1%). Intrinsic motivations for pursuing AST included personal interest, professional growth, and a desire to enhance patient care. However, funding challenges, burnout, and workload were identified as significant barriers to acquiring additional skills. Qualitative analysis identified six themes, three each related to facilitators (desire to work rurally, meeting workforce needs, and support networks) and barriers (work-life balance, mismatched expectations, and inadequate recognition of AST).ConclusionAdditional skills training is a highly valued training program. Most of the GPs who were involved in the program were intrinsically motivated to participate. However, to ensure its sustainability, wider recognition of the value, better visibility, and better alignment with community needs are required.